A modified fluctuation-test framework characterizes the population dynamics and mutation rate of colorectal cancer persister cells - Russo, Mariangela; Pompei, Simone; Sogari, Alberto; Corigliano, Mattia; Crisafulli, Giovanni; Puliafito, Alberto; Lamba, Simona; Erriquez, Jessica; Bertotti, Andrea; Gherardi, Marco; Di Nicolantonio, Federica; Bardelli, Alberto; et al. (Nature genetics, 2022)
Compelling evidence shows that cancer persister cells represent a major limit to the long-term efficacy of targeted therapies. However, the phenotype and population dynamics of cancer persister cells remain unclear. We developed a quantitative framework to study persisters by combining experimental characterization and mathematical modeling. We found that, in colorectal cancer, a fraction of persisters slowly replicates. Clinically approved targeted therapies induce a switch to drug-tolerant persisters and a temporary 7- to 50-fold increase of their mutation rate, thus increasing the number of persister-derived resistant cells. These findings reveal that treatment may influence persistence and mutability in cancer cells and pinpoint inhibition of error-prone DNA polymerases as a strategy to restrict tumor recurrence. A modified fluctuation test applied to colorectal cancer cells shows that EGFR/BRAF inhibitor-induced persisters slowly proliferate and have an increased mutation rate. Error-prone DNA polymerases are identified as potential targets to avoid tumor recurrence following treatment with these drugs.